Hypoxia induces osteogenic/angiogenic responses of bone marrow‐derived mesenchymal stromal cells seeded on bone‐derived scaffolds via ERK1/2 and p38 pathways. (17th January 2013) - Zhou, Yi; Guan, Xiaoxu; Wang, Huiming; Zhu, Zhuoli; Li, Chiquan; Wu, Shu; Yu, Haiyang
Abstract Osteogenesis and angiogenesis are tightly coupled processes during bone development and formation. It is thus well known that the enhancement of vascularization is of great importance in bone tissue engineering. As a potential approach for repairing bone defects, bone tissue constructs should therefore replicate the essential components in vivo microenvironments to promote cell osteogenic differentiation while at same time induce angiogenic response. In light of standpoint above, a combination of human bone‐derived scaffolds and BMSCs that subjected to hypoxia was used to mimic in vivo conditions. Also the underlying cellular/molecular regulation was fully investigated. The results showed that hypoxia (5–10% O2) greatly enhanced the proliferation of BMSCs seeded in scaffolds, although the hypoxia (5% O2)‐induced proliferative effect on BMSC cellular scaffolds was not apparent to those cultured in plates. However, such a kind of model was able to significantly induce the osteogenic/angiogenic responses of BMSCs as reflected by osteogenesis or angiogenesis‐related highly expressed genes or proteins, such as alkaline phosphatase, osteocalcin, hypoxia‐inducible factor‐1α and vascular endothelial growth factor. Moreover, ERK1/2 and/or p38 pathways were demonstrated to play essential roles in hypoxia‐induced osteogenic/angiogenic responses. Our results indicated that the combination of bone‐derived scaffolds, a material that has a three dimensional network structure, and hypoxia, an environment that replicates in vivo BMSCs hypoxic living conditions, may be a potential approach for creating functional tissue‐engineered bone. Biotechnol. Bioeng. 2013; 110: 1794–1804. © 2013 Wiley Periodicals, Inc.